Takayasu’s Arteritis Concurrent with Marfan syndrome Associated with Severe Renovascular Hypertension - Sheikh, Naveen; Safiuddin, Mohammad; Tanni, Afia Zainab; Sultana, Nahid; Sultan, Md Ashraf Uddin; Chowdhury, MSI Tipu (University Heart Journal, 2018)
Marfan syndrome (MS) is a dominantly inherited connective tissue disorder characterized by arachnodactyly, tall stature, the presence of aortic aneurysm, and lens dislocation. Takayasu’s arteritis(TA) is an inflammatory disease often affecting the ascending aorta and aortic arch, causing obstruction of the aorta and its major arteries. The disease commonly presents in the 2nd or 3rd decade of life, often with a delayed diagnosis. The disease is progressive and there is no definitive therapy. We report an unusual case of concomitant Takayasu’s arteritis and Marfan syndrome manifesting bilateral renal artery stenosis and aortic root dilatation. The patient had severe hypertension. The simultaneous presence of TA and MS could be a coincidence, however; the pathogenesis of TA might be linked with autoimmunity induced by abnormal extracellular matrix protein derived from the genetic mutations in MS. University Heart Journal Vol. 13, No. 1, January 2017; 29-32